Transformation of management processes of development companies during the period of environmental reorientation - Shpakova, Н.V.; Shpakov , A.V. (Ways to Improve Construction Efficiency, 2021)
The article discusses options for transforming the actions of management of enterprises in the construction industry on the example of development companies. For this purpose, the concept of "construction development" and their role in the development of the country's investment and construction complex are being clarified. To solve the problems formulated in the article, the need to create mechanisms of compensatory influence on the indicators of business activity of enterprises is scientifically substantiated in order to "secure" their functioning for the period of implementation of national restrictions related to the adaptation of the country's economic model to the main postulates of the strategic plan for sustainable development. In this regard, the organizational advantages of the developers' activities have been analyzed, and the systematization of trend innovations in management related to the country's adaptation policy aimed at introducing the principles of sustainable development in all areas of production activity has been carried out. Analyzed the current state of the domestic development services market. The main types of development and strategies that development organizations can choose to achieve their strategic goals have been determined. The main stages of development activities are outlined, broken down by tasks and business processes. An algorithm for the development and implementation of the concept and strategy of enterprise development based on the greening of production (in particular, construction) is proposed. The use of resonance management methods in managing the development of development activities is substantiated in order to achieve a synergistic effect using a minimum of investment resources. The main reasons for the low interest of investors in environmental projects at the stage of design and construction of construction projects are considered. Comparisons of the strategic goals of various types of development companies have been made and options for the implementation of eco-development have been proposed in order to modernize the Ukrainian production segment. An alternative criterion for the effectiveness of the activities of modern organizations from the point of view of adaptogenesis and ensuring the survival of organizations in the long term is proposed. A theoretical basis has been laid for the formation of an improved organizational and institutional platform for economic management of development processes with the help of resonant management mechanisms in the context of the development of the world economy on the principles of sustainable development.